Chinese arts and crafts - Hang, Jian; Guo, Qiuhui (New York Cambridge University Press, 2012)
This illustrated introduction discusses the colorful history and development of distinctive Chinese crafts, including ceramics, furniture, clothing and decorative arts.
The traditional arts and crafts of China -- Materials for daily use -- Textiles -- Homewares -- Decoration -- Plays and playing -- Commercial arts -- Legends related to arts and crafts -- Traditional crafts in modern China -- Chronological table of Chinese dynasties.
Originally published by China Intercontinental Press as Chinese Arts and Crafts (9787508516080) in 2010.
Keywords: Decorative arts -- China; Handicraft -- China -- History